New phraseological units in poetry poets XV-XVIII centuries (Eurasian Journal of Philology Science and Education, 2015)
This article will identify occasional phraseological differences that occur in the epic and lyric epics, as well as examples of what some random combinations in epic poetry received nation-wide applications such as idioms. In the initial epic poetry Kazakh poetry along with phraseological variants frequent and occasional combinations. The epic poetry devoted poverty, inequality, nature, life and death, the passage of time, art, criticism of Heads of State and biys description of his native land, in such epics can find similarities in content, theme, number of syllables, and rhyme structure. However, due to inherent differences different akyns formed new author or the occasional use of a combination. In some cases, some author idioms akyns obsolete and moved to the passive part of the language, or by revising and updating occur occasional options.
Keywords: idiom; occasionalism; akyn; poetry; random combinations; outdated and updated idioms; occasional combinations